The Concept of a Circular Economy Through the Lens of Sustainable Human Resource Management - Džajic Uršič, Erika; Bernik, Mojca (Sodobni pristopi v kadrovskem managementu in izobraževanju, 2026)
The paper examines the functioning of the circular economy in the field of sustainable human resource management. The concept of a circular economy is often presented as a means of achieving broader economic and social benefits, such as improved well-being, sustainable economic growth, and job creation. A key aspect of this is sustainable human resource management, which aims to ensure a healthy and successful workforce that drives organizational progress through goal achievement. One of the tasks of sustainable human resource management is to reduce the rate of health-related absenteeism, which has both financial and organizational implications for a company. In the context of a circular economy, the goal of sustainable HR management is twofold: on the one hand, to implement preventive measures to reduce absenteeism, and on the other, to establish initiatives that facilitate and accelerate employees' return to work.